Community Education on Clean and Healthy Living Behavior (CHLB) Due to Urinary Tract Infections (UTIs) in Pregnant Women - Nurlina Subair; Haris, Risma; Badawi, Badriani; Marlina (International Journal of Integrative Sciences, 2024)
The implementation of Clean and Healthy Living Behavior (CHLB) plays a crucial role in maintaining the health of pregnant women, particularly in preventing Urinary Tract Infections (UTIs), which can become a serious issue during pregnancy. UTIs may increase the risk of complications such as preterm labor or low birth weight. Data collected from pre-test and post-test assessments indicate a significant increase in knowledge, with initial scores at just 20%, rising to 68% after intervention. Therefore, the implementation of CHLB is essential, encompassing simple habits like regular hand washing with soap, maintaining genital hygiene, and consuming sufficient water to increase urine volume, thereby reducing the risk of UTIs. Additionally, it is important for pregnant women to avoid contracting sexually transmitted infections (STIs), which can increase the risk of UTIs. By effectively practicing CHLB, pregnant women can lower the likelihood of developing UTIs, maintain their own health as well as that of their unborn child, and ensure a smooth pregnancy and delivery process